Bridging human resource management theory and practice: Implications for industry‐engaged academic research - Timming, Andrew R.; Macneil, Johanna (Human resource management journal, 2023)
The link between academic theory and the professional practice of human resource management (HRM) is often tenuous and disjointed. The “gap” between theory and practice is damaging to academics and practitioners. On the one hand, academic research is often highly theoretical and methodologically complex. On the other, HR professionals tend to oversimplify advice on “how to solve” HRM “problems” and they may conduct research lacking rigor and nuance. Insofar as a bridge can be built between HRM theory and practice, significant benefits exist for both parties. Mick Marchington exemplified this bridge. His commitment to pluralism wrought significant influence on the professional practice of HRM through highly readable and practically useful theory. We look to Marchington's work to draw lessons on how we can better bridge theory and practice for the enrichment of academics and practitioners. We develop a framework contrasting “academic esotericism” with “practitioner reductionism.” We then propose a third way: “industry‐engaged academic research.” Practitioner Notes What is currently known about the subject matter? There is a much‐lamented divide between human resource management (HRM) theory and practice. HR academics often research and write for each other and, in doing so, fail to identify issues of importance to practitioners. Similarly, practitioners rely on oversimplified concepts, data, and analysis, which are often neither rigorous, nor generalizable. What this paper adds to this? Mick Marchington was an academic whose commitment to pluralism and applied theory set an example of how to bridge that divide. We articulate a novel framework for understanding, and better integrating, HRM theory and professional practice. Implications of the study findings for practitioners Practitioners benefit from an understanding of Mick Marchington's legacy, in particular his demonstration of the practical value of good theory. Our framework explains how HRM academics can build better relationships with HR professionals. These relationships must be based on rigor, shared values, and a pragmatic approach to HRM theory and practice grounded in common insight.